Aplikasi Sistem Pakar Penyakit Hewan Peliharaan Dengan Metode Forward Chaining - Alim, Ocky Mahendra; Santoso, Leo Willyanto; Noertjahyana, Agustinus (Jurnal Infra, 2015)
With the lack of knowledge about the disease and treatment of animal diseases, animals do not get first aid, if we know the ilness no need to be panic and bring the animal to the doctor to perform further tests.Therefore, to help understand the illness and knowing first aid should be done when a pet suffering from the disease, it takes an application that can help detect what type of disease suffered and help necessary.From the above problems the authors designed a web-based expert system application that can overcome the above problems.